1999
DOI: 10.1021/jo990061j
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Property Relationships in Trimethylenemethane-Type Biradicals. 2. Synthesis and EPR Spectral Characterization of Dinitroxide Biradicals

Abstract: Several trimethylenemethane-type (TMM-type) dinitroxide biradicals have been prepared that differ in tert-butylaminoxylphenyl ring torsion angles by virtue of different steric demands of their "spinprotecting groups". In addition, the synthesis of a TMM-type dinitroxide having a planar π-system is reported. The synthetic route employed for the planar TMM-type biradical is general and should therefore expand the utility of TMM-type biradicals that are susceptible to bond torsions that attenuate exchange couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 45 publications
6
36
0
Order By: Relevance
“…Since no experimental reports of these designed diradicals are available, we here first give two analogues to confirm the feasibility of our design and usability of the calculational methods. Over the past years, Shultz and co‐workers synthesized stable trimethylenemethane analogues which are very similar to our designed diradicals of Etpp and investigated their magnetic properties . Two of them are shown in Figure S2.…”
Section: Resultsmentioning
confidence: 98%
“…Since no experimental reports of these designed diradicals are available, we here first give two analogues to confirm the feasibility of our design and usability of the calculational methods. Over the past years, Shultz and co‐workers synthesized stable trimethylenemethane analogues which are very similar to our designed diradicals of Etpp and investigated their magnetic properties . Two of them are shown in Figure S2.…”
Section: Resultsmentioning
confidence: 98%
“…[17] Keeping the above considerations in mind, compounds a-2 and b-2 were analyzed. Thus, in a-2, the twist angles between the imidazoline and Cp rings are f = À118 and À128, whereas in b-2 both angles f are close to zero, thereby promoting a stronger magnetic exchange interaction between the radical units.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, one-electron reduction of metal complexes of 1 -5 will yield Downloaded by [The University of Manchester Library] at 08:43 09 December 2014 mixed-valent semiquinone-Linker-catecholate complexes, and we can test how conformation modulates delocalization. [46] We have shown that the molecular conformation is affected by the functional groups that cap the Linker: [56] clearly, the p-systems of the EG and Linker in 1 are mutually coplanar, while in 2 and 3 moderate torsion is induced by the norbornyl and quinone groups, respectively. Bis(semiquinone) 4 has even greater torsions, and 5 is a model compound that allows assessment of the C=C as Linker.…”
Section: New Semiquinone-type Ligandsmentioning
confidence: 91%
“…[29] However, relatively little is known about conformational exchange modulation in TMM-type biradicals. [29] To study this important structure-property relationship, we prepared a series of dinitroxide biradicals [56] and bis(semiquinone) ligands 1 -5. X-ray crystallographic analysis and magnetometry are nearly complete on the dinitroxide series of molecules and will be reported soon.…”
Section: New Semiquinone-type Ligandsmentioning
confidence: 99%